UPAYA MENINGKATKAN KEMAMPUAN MEMBACA DAN MENULIS KALIMAT SEDERHANA SISWA KELAS II B MATA PELAJARAN BAHASA INDONESIA MATERI SAYANG LINGKUNGAN MELALUI PENERAPAN MODEL PjBL DI SDN SN KEBUN BUNGA 4 BANJARMASIN - Raharjo, Kurniawan Tri; Hayati, Rahmah; Alma Nur Rizki, Dita; Yusniarti; Fazriah, Nurul; Rachman, Ali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low reading and simple sentence-writing skills of Grade II B students at SDN SN Kebun Bunga 4 Banjarmasin. Students experienced difficulties in understanding simple texts and constructing sentences independently. The purpose of this study was to improve students' reading and simple sentence-writing skills through the implementation of the Project Based Learning (PjBL) model. This study employed Classroom Action Research (CAR) conducted in three meetings involving 22 students as the research subjects. Data were collected through observation, tests, and documentation. The data were analyzed using descriptive comparative analysis by comparing the results from each meeting. The findings showed improvements in reading skills, writing skills, and learning outcomes. Reading skills increased from 9.1% in the first meeting to 36.4% in the second meeting and 77.3% in the third meeting. Writing skills improved from 22.72% to 63.63% and 86.37%, while learning outcomes increased from 36.36% to 60% and 90%. These results indicate that the implementation of the Project Based Learning (PjBL) model was effective in improving students' reading skills, simple sentence-writing skills, and learning outcomes